Development of a complex intervention to prevent delirium in older hospitalized patients by optimizing discharge and transfer processes and involving caregivers: a multi-method study - Denninger, Natascha-Elisabeth; Brefka, Simone; Skudlik, Stefanie; Leinert, Christoph; Mross, Thomas; Meyer, Gabriele; Sulmann, Daniela; Dallmeier Rojas, Dhayana Elizabeth; Denkinger, Michael D.; Müller, Martin (International journal of nursing studies, 2024)
Complex intervention, Delirium, Caregivers, Family, Acute care, Hospitals, Patient care management, Patient discharge, Patient transfer
Gesehen am 22.08.2024
Early access: December 2023